Preclinical Bioavailability Assessment of a Poorly Water-Soluble Drug, HGR4113, Using a Stable Isotope Tracer - Eun Ji Ha; Jeong In Seo; Shaheed Ur Rehman; Hyung Soon Park; Sang-Ku Yoo; Hye Hyun Yoo (MDPI AG, 2023)
Drug solubility limits intravenous dosing for poorly water-soluble medicines, which misrepresents their bioavailability estimation. The current study explored a method using a stable isotope tracer to assess the bioavailability of drugs that are poorly water-soluble. HGR4113 and its deuterated analog, HGR4113-d7, were tested as model drugs. To determine the level of HGR4113 and HGR4113-d7 in rat plasma, a bioanalytical method using LC-MS/MS was developed. The HGR4113-d7 was intravenously administered to rats that were orally pre-administered HGR4113 at different doses; subsequently, the plasma samples were collected. HGR4113 and HGR4113-d7 were simultaneously determined in the plasma samples, and bioavailability was calculated using plasma drug concentration values. The bioavailability of HGR4113 was 53.3% ± 19.5%, 56.9% ± 14.0%, and 67.8% ± 16.7% after oral dosages of 40, 80, and 160 mg/kg, respectively. By eliminating the differences in clearance between intravenous and oral dosages at different levels, acquired data showed that the current method reduced measurement errors in bioavailability when compared to the conventional approach. The present study suggests a prominent method for evaluating the bioavailability of drugs with poor aqueous solubility in preclinical studies.